Microstructure elucidation of polyflavonoid tannins by MALDI‐TOF‐CID. Issue 3 (10th May 2012) - Radebe, Nonhlanhla; Rode, Karsten; Pizzi, Antonio; Pasch, Harald
Abstract: High molar mass wood tannin extracts are complex mixtures that are distributed in both molar mass and chemical composition. Condensed tannins from quebracho and mimosa woods were analyzed and compared with cacao tannins using matrix‐assisted laser desorption/ionization‐time of flight (MALDI‐TOF) mass spectrometry. Although MALDI‐TOF MS reveals the oligomer structure of the tannins, this method cannot distinguish between isomers with isobaric masses, and therefore, ambiguous structural assignments were made in a number of cases. To determine the actual microstructures present, MALDI‐TOF collision‐induced dissociation (CID) experiments were conducted. MALDI‐TOF‐CID enables monomer sequence determination, and positive assignments of isobaric structures can be made. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :